2017
DOI: 10.1016/j.msea.2017.03.061
|View full text |Cite
|
Sign up to set email alerts
|

In situ synchrotron X-ray diffraction study of deformation behaviour of a metastable β-type Ti-33Nb-4Sn alloy

Abstract: In this study, the deformation behaviour of metastable β-type Ti-33Nb-4Sn alloys in different thermo-mechanical treatment states is investigated by tensile tests and in situ synchrotron X-ray diffraction (SXRD). In the case of solution-treated alloy, stress-induced martensitic (SIM) transformation takes place over a wide strain range of 0.5-14%. During this SIM transformation, the parameter of b α" ([020] α") increases with macroscopic strain within strain range of 1.5-4.7%, giving rise to that the α" variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Therefore, to study the shape memory behavior of Ti-Nb alloy, the mass percentage of Nb element should be less than 34 mass%; to obtain a relatively stable β-type phase content, the mass percentage of Nb content is generally greater than 34 mass% [6]. In ternary Ti-Nb-Sn alloys, the addition of Sn can adjust the mass percentage of Ti and Nb, and then adjust the content of martensite, allow the study of the shape memory behavior and/or superelasticity of different components, and the mechanical properties of β-type Ti-Nb-Sn alloys [31,[33][34][35]. Wang [30] reported that in ternary Ti-Nb-Sn alloys, the content of martensite decreases with the increase of Sn content, and decreases with the decrease of corresponding Ti content, indicating that stable β-type Ti-Nb-Sn alloys can be obtained by adjusting the Ti and Sn contents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to study the shape memory behavior of Ti-Nb alloy, the mass percentage of Nb element should be less than 34 mass%; to obtain a relatively stable β-type phase content, the mass percentage of Nb content is generally greater than 34 mass% [6]. In ternary Ti-Nb-Sn alloys, the addition of Sn can adjust the mass percentage of Ti and Nb, and then adjust the content of martensite, allow the study of the shape memory behavior and/or superelasticity of different components, and the mechanical properties of β-type Ti-Nb-Sn alloys [31,[33][34][35]. Wang [30] reported that in ternary Ti-Nb-Sn alloys, the content of martensite decreases with the increase of Sn content, and decreases with the decrease of corresponding Ti content, indicating that stable β-type Ti-Nb-Sn alloys can be obtained by adjusting the Ti and Sn contents.…”
Section: Introductionmentioning
confidence: 99%
“…In immersion test, the ions (Na + , K + , Mg 2+ , Ca 2+ , Cl − , HCO 3− , HPO 4 2− and SO 4 2− ) in the simulated physiological solution would react with the released ions (Ca 2+ , Ti x+ , Nb x+ and P x− ) in composites, forming various compounds. The composites, according to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] Among them, Zr received renewed attention for surgical implants because it shows acceptable mechanical strength, satisfactory biocompatibility and corrosion resistance. In addition, Zr is a neutral element when dissolved in Ti and it can improve the strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…例如, 在 口香糖钛合金(Gum-Metal)应变玻璃中, 实现了热膨胀 系数的调控和Invar效应 [22] ; 在Ti-Ni, Ti-Ni-Fe基应变玻 璃合金中, 实现了不基于自发马氏体相变而是由应变 玻璃的应力诱发马氏体相变产生的新形状记忆效 应 [5,6] . 在此现象中, 低温无序分布的纳米马氏体畴被 ; 以及在Ti-Nb基应变 玻璃合金中, 实现了宽温域超弹性 [8][9][10][11] 、低模量超弹 性 [23][24][25] [26,[29][30][31] , 两者在相变区间都表现出弹性模量的异 常 [26,27,32,33] . 了解铁磁应变玻璃与预马氏体的区别与 [29] .…”
unclassified